The optimization of semiconductor light, generating white light, heating regime - Jurgita Dabulytė; Feliksas Ivanauskas (Lietuvos Matematikos Rinkinys)
In this work the mathematical model of semiconductor light was employed. There were offered the distribution cases for monochromatic lighting sources.